A REVIEW OF THE EFFECTS OF WASTEWATER ON REINFORCED CONCRETE STRUCTURES IN NIGERIA (Nigerian Journal of Technology, 2016)
This paper reviews the degradation mechanism of wastewater on reinforced concrete structures with a view to finding what needs to be done to salvage these structures. Potential disintegrating agents in wastewater generated in Nigeria were identified and common degradation effects were examined. Regeneration, preventive and corrective techniques were noted. While noting that poor maintenance culture, lack of multidisciplinary research work and high cost of maintenance were major factors responsible for the high rate of deterioration. The paper, therefore, concluded with suggestions that could be employed to salvage these structures from total collapse. One of such approaches is to use admixtures, which could reduce the effect of acidic attack common in wastewater concrete structures. http://dx.doi.org/10.4314/njt.v35i2.2